Perspectives on optimizing microalgae cultivation: Harnessing dissolved CO2 and lactose for sustainable and cost-efficient protein production - Sunni Chen; Honglin Zhu; Emily Radican; Xinhao Wang; Dennis J. D'Amico; Zhenlei Xiao; Yangchao Luo (Journal of Agriculture and Food Research)
Microalgae, known for their land-sparing cultivation and remarkable photosynthetic efficiency, play a crucial role in advancing sustainable development goals. This study explored the use of cost-effective inorganic carbon (the ionic form of CO2) and organic carbon sources (lactose, a primary sugar in whey wastewater) to support the growth of Chlorella sorokiniana UTEX 1230, and improved protein content through nitrogen supply optimization. NaHCO3 proved to be more effective than Na2CO3, resulting in a 3.4-fold increase in biomass concentration, with an initial 5 mM HCO3‾ concentration compared to the basal medium. Further addition of 0.75 % lactose led to a 4.05-fold increase in biomass concentration, with the maximum specific growth rate at 1.28/d, maximum biomass concentration at 695.88 mg/L, and maximum biomass productivity at 250.91 mg/L/d. Nitrogen supplementation greatly increased protein concentration from 16.41 % (250 mg/L NaNO3) to 52.95 % (1000 mg/L NaNO3). These results support the potential for utilizing whey wastewater bioremediation to produce high-value protein via microalgal cultivation.